The World Health Organization (WHO) Integrated Care for Older People (ICOPE) framework: a narrative review on its adoption worldwide and lessons learnt - Sum, Grace (2023)
The World Health Organization (WHO) recently published guidelines on the implementation of a new Integrated Care for Older People (ICOPE) framework in 2017-2019. It is an integrated care framework for the screening, assessment, and management of intrinsic capacity (IC) declines. We aimed to examine where the early adopters of ICOPE are across the world, how these study teams and sites plan to apply the framework or have applied it, and the lessons learnt for future adopters. We systematically searched electronic medical and social sciences databases and grey literature published between 31 October 2017 and 31 March 2022. Records were systematically selected using precise inclusion criteria. There were 18 ICOPE study teams and sites across the 29 selected records. Of the 18 study teams and sites, seven were in the development stage, seven conducted feasibility studies, and four have commenced implementation of interventions that applied the ICOPE framework. Future ICOPE adopters may need to make certain decisions. These include whether to adopt ICOPE in the community setting or other settings, whether to adopt only Step 1 on IC screening or additional ICOPE Steps, whether the ICOPE IC screening tool requires modifications, and whether to use digital health technology. We propose the key factors needed to make these decisions and future research needed.